PENDAMPINGAN DIGITAL MARKETING AIR MINUM DALAM KEMASAN SEBAGAI STRATEGI PERLUASAN PASAR PADA BUMDES DESA WASILOMATA II KABUPATEN BUTON TENGAH - Rais, Muhammad; Zarliani Uli, Nur; Adan, L.M. Hasrul; Fadila, Nihla (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Wasilomata II Village is one of the administrative villages in Mawasangka Subdistrict, Central Buton Regency, which has abundant natural resources, especially in the cave water source sector. However, this potential has not been optimized by the Village-Owned Enterprise (BUMDes) as a strategic village economic institution. This community service activity aims to assist the Village-Owned Enterprise (BUMDes) of Wasilomata II Village in optimizing the use of digital marketing as a strategy to expand the market for bottled drinking water (AMDK). The method of implementation of this activity uses a participatory approach through several stages, namely: (1) observation and identification of BUMDes problems; (2) digital marketing training for BUMDes administrators; (3) technical assistance in creating official BUMDes accounts and managing promotional content; (4) strategy implementation; and (5) program monitoring and evaluation. All activities are carried out collaboratively with village partners, BUMDes administrators, community leaders, and the village community. The expected outcomes of these activities are an increase in BUMDes administrators' understanding of digital marketing, the creation of official BUMDes accounts on several online platforms, and an increase in the marketing reach of bottled water products. These activities are expected to encourage village economic independence through the sustainable use of digital technology. The purpose of this assistance is to increase the capacity of the management of the Village-Owned Enterprise (BUMDes) of Wasilomata II Village in implementing digital marketing strategies as an effort to expand the market for bottled drinking water (AMDK) products.